The deal.II code gallery: Quasi-static Finite-Strain Quasi-incompressible Visco-elasticity - Pelteret, Jean-Paul (2017)
Quasi-static finite-strain quasi-incompressible rate-dependent elasticity computing the displacement history of a thin viscoelastic strip with a hole.
Keywords: Finite elements; Finite strain nonlinear visco-elasticity; Quasi-incompressibility; Mixed methods